Identifikasi Kendala Pendidik Dalam Pembelajaran IPA Terpadu Di SMP Se-Kabupaten Pringsewu - Apsah Gatin Lestari; Darlen Sikumbang; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
This study aims to identify difficulties of science teachers of junior hight school at Pringsewu in the Academic Year of 2018/2019. The difficulties included the planning, implementing, assessment, and educational background of teacher. Thus, all science teachers of junior hight school that were selected by purpose sampling technique. This research design was descriptive. Qualitative data were obtained from  questionnaire and interviews  were analysis descriptively. The research result showed that the difficulties of science teachers in planning the learning were classified as low difficult to indicators develop curriculum, teaching materials, and learning methods and strategies. The difficulties in implementing the learning were indicators of preliminary, core, closing, and learning sites was low criteria. The difficulties in assessments the planning and  implementing assessments were indicators of was low criteria. The difficulties in education background teachers to indicators planning, implementing, and assessments was low criteria.  So, teachers difficulties in planning, implementing, assessments, and  teacher background education had low criteria.Penelitian ini bertujuan mengidentifikasi kendala  pendidik dalam pembelajaran IPA terpadu SMP se-Kebupaten Pringsewu tahun ajaran 2018/2019. Sampel penelitian ini adalah pendidik yang dipilih  dengan teknik purpose sampling. Desain penelitian adalah deskriptif. Data Kualitatif diperoleh dari penyebaran angket, wawancara pendidik dalam pembelajaran IPA terpadu dan latar belakang pendidikan pendidik. Hasil penelitian menunjukkan kendala pendidik  IPA dalam merencanakan pembelajaran pada indikator mengembangkan kurikulum, bahan ajar, metode dan strategi pembelajaran tergolong rendah. Kendala dalam melaksanakan pemebelajaran pada indikator kegiatan pendahuluan, inti, penutup, dan tempat pembelajaran tergolong rendah. Kedala dalam penilaian pembelajaran pada indikator perencanaan dan pelaksanaan tergolong rendah. Kendala pada latar belakang pendidikan pendidik dalam  pembelajaran IPA terpadu memiliki kriteria rendah. Jadi, kendala pendidik dalam merencanakan, melaksanakan, penilaian, dan latar belakang pendidikan pendidik dalam pembelajaran IPA terpadu memiliki kriteria rendah. Kata kunci: IPA terpadu, kendala, pembelajaran, pendidik